Glaucoma the Silent Thief of Vision! A Study to Assess Current Trends on Awareness and Knowledge About Glaucoma - Jain, Amit Kumar; Singh, Neha; Singh, Naveen Kumar; Singh, Praveen Kumar; Rajpoot, Suman (Annals of the National Academy of Medical Sciences (India), 2023)
Introduction Worldwide nearly 70 million populations are affected by glaucoma, a leading cause of irreversible blindness. Awareness and knowledge about glaucoma is the key to early diagnosis and effective management to prevent debilitating blindness. In India, the literature has shown that the level of awareness ranges from 0.32 to 13.5%, much lower than developed countries. Previous studies found higher levels of education and socioeconomic status along with positive family history of ocular diseases were directly related to improved levels of awareness and knowledge about glaucoma. Considering the improvement in literacy standards, socioeconomic status, and better utilization of medical care in the past few years, we aimed to assess the current trends in levels of awareness and knowledge about glaucoma in the North Indian population.Methodology This prospective cross-sectional questionnaire-based study included 1,536 participants enrolled from the outpatient department of a tertiary care teaching hospital. Data for the study were collected from the responses given by participants from two sets of questionnaires adopted and validated from previous similar work on awareness of glaucoma. Statistical analysis was done by applying the chi-square test and Fisher exact probability test using IBM SPSS Statistics version 20.Results In total, 7.74% of study participants were aware of glaucoma and the newspaper was the most common source of (57.9%) information. A significant correlation (p < 0.05) was found for male sex, education status, and past medical history between aware and not aware participants; however, non-significant (p = 0.182) correlation was seen for upper and lower socioeconomic status among the same group participants. Only 16% of aware participants had a good knowledge of glaucoma.Conclusion In current trends, the state of awareness and knowledge on glaucoma in the Indian population was poor compared to that in the Western world, although the levels of education status and the presence of past medical history had significant correlation among aware and not aware population, but socioeconomic status had no significant correlation. Electronic media and health camps were among the least common source of information; hence, improvised awareness programs and opportunistic screening of glaucoma is the answer to control this silent thief of vision called glaucoma.
Keywords: Glaucoma; awareness; knowledge; literacy; north India